Kemampuan Firm Size dan Laverage Terhadap Bond Rating pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Fabianca Fachreza; Nor Norisanti; Acep Samsudin (Politeknik Negeri Bengkalis, 2020)
This study aims to examine the effect of Firm Size and Leverage on Bond Ratings in banking subsector companies in the Indonesia Stock Exchange period 2018. The sample in this study was obtained using purposive sampling method which is included in the non-probability sampling technique. The sample in this study consisted of banking subsector companies listed on the IDX in 2018 and rated by PT PEFINDO with a total of 22 banking companies. The method used in this research is descriptive with quantitative and associative approaches. The data analysis technique used is multiple linear regression analysis with an R Square value of 0.030 which can be interpreted as the effect of firm size and leverage on a bond rating of 3% and the remaining 97% is influenced by other factors not examined in this study. F Test results show a value of Fcount 0.295 <3.49 Ftable which means there is no effect on firm size and leverage on the bond rating. From the test results partially firm size variables have a positive effect and leverage has a negative effect on the bond rating.